2017
DOI: 10.1002/2017tc004696
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Zircon Provenance Constrain Age and Geometry of an Early Paleozoic Rift in the Pinjarra Orogen, East Gondwana

Abstract: The Tumblagooda Sandstone in Western Australia documents Early Paleozoic rifting in East Gondwana and provides the earliest evidence for terrestrial activity of multicellular animals on Earth. We constrain the provenance of this sequence using 737 concordant U–Pb ages of detrital zircons from two stratigraphic wells in the northern Perth Basin and Southern Carnarvon Basin and outcrops of the type sections near Kalbarri. Detrital zircon age signatures are linked to infrared spectral data and stratigraphic logs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Previous studies of ichnotaxa initially suggested a similarity to the Devonian Taylor Group (Trewin & McNamara, 1994). Recent work by Markwitz et al (2017) on detrital zircon ages also supports a middle Ordovician age for deposition of 466 AE 8 Ma placing it firmly in the time prior to the evolution of rooted land plants.…”
Section: Geological Settingmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies of ichnotaxa initially suggested a similarity to the Devonian Taylor Group (Trewin & McNamara, 1994). Recent work by Markwitz et al (2017) on detrital zircon ages also supports a middle Ordovician age for deposition of 466 AE 8 Ma placing it firmly in the time prior to the evolution of rooted land plants.…”
Section: Geological Settingmentioning
confidence: 87%
“…Recent work by Markwitz et al . () on detrital zircon ages also supports a middle Ordovician age for deposition of 466 ± 8 Ma placing it firmly in the time prior to the evolution of rooted land plants.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Detrital zircon dates from the Tumblagooda Sandstone set a maximum possible age at 466 ± 8 Ma (Markwitz et al 2017). When considered alongside the c. 430 Ma Rb-Sr ages for regional uplift across SW Australia (Libby & De Laeter, 1998;McNamara, 2014), which were dated using biotites from the Yilgarn Craton (a minor provenance source for the Tumblagooda Sandstone; Figure 1 is highlighted by the blue box.…”
Section: A Agementioning
confidence: 99%
“…However, the calculated alpha dose per gram provides a sensible estimate of the radiation damage only if the zircon structure has experienced no signicant annealing of radiation damage since crystallization, 106,107 and obtaining FWHM values for individual crystals is only feasible for a limited number of grains representative of magmatic populations 99,102 and is not practical for detrital studies, for example, where >120 grains per sample are oen analyzed to derive statistically signicant population distributions (e.g., ref. [105][106][107][108][109].…”
Section: Ion Counter Correctionsmentioning
confidence: 99%